The Effect Light of the Container and the Feeding Rate on Growth and Survival Rate of Snakehead Fish Larvae (Channa striata Bloch, 1793) - Syahrul Reza; Netti Aryani; Nur Asiah (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2024)
This research aimed to determine the best light on the container and the feeding rate on the growth and survival of snakehead fish larvae. This research was carried out in March-April 2022 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This research method used a Completely Randomized Design with two factors and three replications. The first factor was the different Lights of the container, which were on two levels. The second factor is the feeding rate, which has three levels. The treatments in this study, namely WtP40 (light and feeding rate 40), WtP50 (light and feeding rate 50), WtP60 (light and feeding rate 60), WgP40 (dark and feeding rate 40), WgP50 (dark and feeding rate 50), WgP60 (dark and feeding rate 60). The results showed that the container's light and the feeding rate had a significant effect (P < 0.05) on the growth and survival of snakehead fish larvae. The results showed that dark containers with a feeding rate of 60% provided a high growth and survival rate in snakehead fish larvae rearing.